Prediction of peritoneal soiling in acute appendicitis with simple clinical and laboratory data. Prospective, multicenter, cohort study of 2, 645 adult patients nationwide. (August 2022) - Lluís, N.; Parra, J.; Villodre, C.; Zapater, P.; Jalali, A.; Cantó, M.; Mena, L.; Ramia, J.M.; Lluís, F.; ,; Afonso, N.; Aguilella, V.; et al.
Abstract: Background and aims: In order to facilitate the preoperative prediction of complicated appendicitis, we propose a complementary approach by selecting an endpoint defined by the intraoperative finding of peritoneal soiling (PS). Methods: Over a 6-month period, 38 centers (5% of all public hospitals) attending emergency general surgery patients on a 24-h, 7-days a week basis, enrolled consecutive adult patients requiring appendectomy. Patients were stratified according to the absence or the finding of PS during the surgical procedure. Results: A total of 2645 patients were included; median age (IQR) was 35 (22–51) years, 44.3% were female. The laparoscopic approach was used in 70.8% of appendectomies. In a third of patients (31.7%), there was PS with pus around the appendix, or bowel contents, free pus, or blood in the peritoneal cavity. To develop the prediction model, 1764 patients were randomly selected for the derivation cohort and the remaining 881 patients were assigned to the validation cohort. On multivariable logistic regression analysis of all patients, two clinical variables (age, and pulse) and three laboratory variables (serum urea, serum sodium, and white blood cell count) were individually associated ( P  < .05) with a greater probability of having PS (Hosmer-Lemeshow chi, 1.63; P  = .99; C-statistic, 0.7). Based on the multivariable regression model, both static and dynamic nomograms were developed for the prediction of PS in patients with acute appendicitis. Conclusions: The entry of simple clinical and laboratory variables in the dynamic nomogram may be useful in guiding the initial management of patients with acute appendicitis in resource-limited settings. Highlights: Mortality from complicated appendicitis still high in underserved areas of the world. The study offers a dynamic nomogram to predict peritoneal soiling in appendicitis. The nomogram employs simple, readily available clinical and laboratory data. Age, pulse rate, serum urea, serum sodium, and white cell count are required. Prediction of complicated appendicitis made feasible in resource-limited settings.